How We Hear: The Perception and Neural Coding of Sound - Oxenham, Andrew J. (Annu Rev Psychol, 2017)
Auditory perception is our main gateway to communication with others via speech and music, and it also plays an important role in alerting and orienting us to new events. This review provides an overview of selected topics pertaining to the perception and neural coding of sound, starting with the first stage of filtering in the cochlea and its profound impact on perception. The next topic, pitch, has been debated for millennia, but recent technical and theoretical developments continue to provide us with new insights. Cochlear filtering and pitch both play key roles in our ability to parse the auditory scene, enabling us to attend to one auditory object or stream while ignoring others. An improved understanding of the basic mechanisms of auditory perception will aid us in the quest to tackle the increasingly important problem of hearing loss in our aging population.